Assessment Factors of Energy Efficiency Measures in Green Building Systems of Hospital Buildings in Palu City - Clara Zenicha Lioni; Tutang M. Kamaludin; Rezky Susmono Karuru; Agnes Christin A Lande; Zet Mallisa (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Green building is the concept of environmentally friendly green buildings that are able to support themselves, save water and energy, and use renewable energy to protect the environment from increasingly severe damage. This research aims to determine the factors that influence energy efficiency and to determine the application of energy efficiency in green building systems for hospital buildings in Palu City. Research data was collected through surveys and interviews by conducting a checklist interview table containing 7 energy efficiency assessment parameters, namely building envelope, ventilation system, air conditioning system, lighting system, transportation system in the building, energy efficiency calculation and electrical system. There were 5 respondents representing the three hospitals studied. Then it is analyzed using the percentage value obtained from each interview table that gets points. The highest results from the percentage values obtained from three hospitals, namely Anutapura Hospital, Anutapura Medical Center (AMC) Building, received a percentage value of 58% for implementing energy efficiency in the green building system.